Tanggung Jawab Notaris Terhadap Akta Kuasa Menjual Dalam Peralihan Hak Atas Tanah - Anishya Yulia Anggraini; Busyra Azheri; Yussy Adelina Mannas (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This study aims to determine the responsibility of a notary for a power of attorney to sell in the transfer of land rights and differences in consideration of the decisions of judges of first instance, judges of appellate level and judges of final instance in judicial review based on Supreme Court decision Number 20 PK/Pid/2020. This study uses a normative juridical research method, with a conceptual and statutory approach. The technique of collecting data is by studying literature relevant to legal issues and then analyzing it qualitatively. This study concludes that the notary Ketut Neli Asih can only be subject to administrative sanctions that adhere to the principle of responsibility based on fault (based on fault of liability), so that the notary concerned cannot be held criminally responsible, because the notary performs his duties as a public official. The verdict of the Panel of Judges of the First Level and the Panel of Judges of the Appellate Level are of the opinion and believe that the actions committed by Ketut Neli Asih as a notary have fulfilled the elements of a crime Article 378 jo. Article 56 paragraph 2 of the Criminal Code, namely "Deliberately Providing Opportunities or Means in the Crime of Fraud". Meanwhile, the Panel of Judges of the Supreme Court who tried the review was of the opinion and believed that the charges charged by the Public Prosecutor were true and proven, but it was not a crime, but rather an administrative matter.